Carrinho industrial multiuso - SILVA, Alexandre da; LOPES, Otavio Augusto; BATISTA, Rogelio Sebastião Aparecido; LUZ, Thiago Carvalho (060, 2022)
O objetivo desse trabalho é simplificar e otimizar a forma como é feita a limpeza dos tornos ao final de cada aula na nossa oficina mecânica. Nosso projeto consiste em criar um carrinho de fácil manuseio onde todas as ferramentas de limpezas estejam acopladas a ele e que todo material descartado fique devidamente separado no lugar destinado.

The objective of this work is to simplify and optimize the way in which the cleaning of the lathes is carried out at the end of each class in our mechanical workshop. Our project consists of creating an easy-to-handle cart where all cleaning tools are attached to it and all discarded material is properly separated in the intended place.
multipurpose industrial trolley
Keywords: Mecânica; Controle e Processos Industriais